RUSSIA'S NUCLEAR DOCTRINE – DETERRENCE FOR THE 21ST CENTURY - Simikic, Sinisa (Politeia, 2025)
The revised Russian nuclear strategy was adopted on November 19, 2024, as a response to the earlier U.S. authorization allowing Ukraine to target deep into Russian territory with medium-range missiles. The prelude to this development was the withdrawal of both the U.S and Russia from strategic arms control agreements. Additionally, following Donald Trump’s victory in the presidental elections, the outgoing U.S. administration futher emphasized support for Ukraine as a foreign policy priority. Seeking continued opposition to the Russian military, Ukraine had, for months during 2024, requested its allies to supply and authorize the use of medium-range missiles for strikes deep into Russian territory, as well as to deliver F-16 fighter jets. The central argument of this paper is that Russia’s revised nuclear doctrine has been adapted to modern wartime conditions and the challenges of the 21st-century international order, serving as a consistent extension of its nuclear deterrence strategy. The new nuclear doctrine, like its predecessor, is based on the nuclear triad. The paper analyzes changes in warfare in the 21st century, emphasizing the widespread use of unmanned aerial vehicles (UAVs), including drones. Furthermore, the goal of the paper is to understand the reasons behind the revision of Russia’s nuclear doctrine, as well as its content and possible implications for international relations.
Keywords: Russia; nuclear doctrine; deterrence; USA; nuclear triad; realism